Comparing the development of agricultural technology and information technology in rural Vietnam - Heidi Kaila (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2015)
This paper presents a descriptive analysis on the ownership of different types of technology - both agricultural machinery and information technology - within households in rural areas of Vietnam. We find that there has been little development in the ownership of agricultural machinery, but a rapid expansion of information technology, especially phones. Households without phones or internet access are more likely to be poor, female-headed, have less education, and rely more on transfers. When controlling for a number of household characteristics including income, households that already own technology are likely to acquire more, suggesting that there are households that are particularly tech-savvy.
Keywords: Q16; O33; 330; technology adoption; internet; mobile phones; agricultural machinery; Vietnam